(untitled) (Proceedings of the Global Public Health Conference, 2025)
Gunungkidul District Early System was notified by the Paliyan Public Health Center about a rise in cases of sudden fever and arthralgia in the week of the 22nd. A team of the District Health Office and Paliyan Public Health Center’s staff and FETP UGM residents conducted an epidemiological investigation.We used 1:1 unmatched case-control study design. Cases were defined as individuals with fever and arthralgia, with/without positive chikungunya lab results, who lived in Pampang Village, Paliyan Sub-district. The controls were healthy residents in the same neighborhood with cases. The total sample was 184 (92 cases and 92 controls). In-depth interviews and observation with structured questionnaires were used for data collection demographics, risk factors, and environmental data. Blood samples were tested using Rapid Diagnostic Test at a health laboratory. The analysis involved chi-square and multiple binomial regression methods.The majority of the cases were female (57.6%), with an age group of 19-59 (58.7%), and residents living in the neighborhood of RT 10/RW 03 (35.9%). All cases had fever and arthralgia. More than half had headaches (59.8%), rash (40.2%), and nausea (22.8%). Eleven samples were tested positive for Chikungunya. The House Index (HI) for larvae is 28.97%. The presence of mosquito larvae around the house (aOR=2.12; 95% CI=1.36 – 2.87) and the habit of collecting rainwater (aOR=1.68; 95% CI=1.02 – 2.45) were associated with higher illness risk in this outbreak. A chikungunya outbreak occurred in Gunungkidul District from 15 May 2024 to 5 August 2024, was linked to mosquito larvae presence and the community’s rainwater collection habit. Education and promotion of health behaviors and implementation of the comprehensive 3M Plus Mosquito Nest Eradication Program (PSN) must be improved